TANTANGAN DAN HARAPAN GURU ABK DI SKHN 01 SERANG DI DUNIA PENDIDIKAN ANAK TUNAGRAHITA - Yahdinil Firda Nadhirah; Siti Kholidah (STKIP Subang, 2026)
Education plays a central role in shaping an inclusive and equitable future, particularly for children with special needs such as those with intellectual disabilities (commonly referred to as